Предмет: Алгебра,
автор: nastyya22
Решите уравнение : 1) х-7+5 ( 3,6-2 (х-3) ) = 1 ;
Ответы
Автор ответа:
0
х - 7 + 5(3,6 - 2(х - 3)) = 1
х - 7 + 5(3,6 - 2х +6) = 1
х - 7 + 18 - 10х + 30 = 1
- 9х + 41 = 1
- 9х = - 41 + 1
9х = 40
х = 4 4/9
х - 7 + 5(3,6 - 2х +6) = 1
х - 7 + 18 - 10х + 30 = 1
- 9х + 41 = 1
- 9х = - 41 + 1
9х = 40
х = 4 4/9
Автор ответа:
0
Спасибо большое )))
Похожие вопросы
Предмет: Алгебра,
автор: dfgfdgg345
Предмет: Литература,
автор: Karolina5647
Предмет: Русский язык,
автор: bergenovaziza
Предмет: Геометрия,
автор: V0lha